Hate and the ‘Jewish Science’ - Frosh, S. author. aut Link
VI, 234 p.
Keywords: Psychoanalysis has always grappled with its Jewish origins, sometimes celebrating them and sometimes trying to escape or deny them. Through exploration of Freud's Jewish identity, the fate of psychoanalysis in Germany under the Nazis, and psychoanalytic theories of anti-Semitism, this book examines the significance of the Jewish connection with psychoanalysis and what that can tell us about political and psychological resistance, anti-Semitism and racism.